Nanoarchitectonics of three-dimensional ZnO–BiVO4 for trace nitrogen dioxide gas detection. Issue 6 (15th March 2022) - Zhu, Zhen; Hsieh, Chia-Ying; Chiang, Zong-Xian; Lin, Yu-Syuan; Wu, Ren-Jang
Abstract: In the present study, several novel three-dimensional (3D) ZnO–BiVO4 composites were prepared using the hydrothermal method, and their ability to detect nitrogen dioxide (NO2 ) gas was assessed. The fabricated sensing materials were examined using X-ray diffraction, transmission electron microscopy, energy dispersive spectrometry, scanning electron microscopy, ultraviolet–visible spectrophotometry, X-ray photoelectron spectroscopy, and surface-area and porosity analysis. The sensing material assessments verified that 3D ZnO–BiVO4 was successfully prepared; the sensing data revealed that 3D ZnO–BiVO4 exhibited excellent sensing response (24.6) to 1-ppm NO2 at room temperature. The composites exhibited a fast response (28 s) and short recovery time (75 s) when detecting 1-ppm NO2 ; they also exhibited long-term stability (decline of approximately 7% after 30 days) and selectivity to 10-ppm NO2 gas. A reasonable NO2 gas sensing mechanism for 3D ZnO–BiVO4 heterojunction was also proposed in this paper.